Clinical and Pathological Study of the First Outbreak Cases of African Swine Fever in Vietnam, 2019 - Nga, Bui Thi To; Tran Anh Dao, Bui; Nguyen Thi, Lan; Osaki, Makoto; Kawashima, Kenji; Song, Daesub; Salguero, Francisco J.; Le, Van Phan (Frontiers in Veterinary Science, 2020)
African swine fever (ASF) is a devastating disease of swine and the most important disease for the pork industry. Since the outbreaks in 2007 in the Caucasian region, it has been spreading to the West and East quite swiftly. In this study we have analysed the clinical signs and pathological features of the first outbreaks on ASF in Vietnam in 2019, caused by an isolated with 100% similarity to the genotype II (p72) isolates from Georgia in 2007 and China in 2018. The disease onset with a peracute to acute clinical course with high mortality. Some animals showed very unspecific clinical signs with other showing severe hyperthermia, respiratory distress, diarrhoea or vomit. Haemorrhagic splenomegaly and lymphadenitis were the main lesions observed at post mortem examination, with histopathological changes confirming the lymphoid depletion and multiorganic haemorrhages. Monocyte-macrophages were identified by means of immunohistochemical methods as the main target cell for the ASF virus in tissue sections.